Evaluation of the sub-lethal toxicity of bleached kraft pulp mill effluent to carassius auratus and dicentrarchus labrax - Diniz, Mário S. (2019)
The effluents from bleached Kraft pulp mill (BKME) and paper industry are toxic to different aquatic organisms being an important source of contamination to aquatic environments due to the presence of several chemicals produced during the production of Kraft pulp. The main objective of the present study was to evaluate the exposure effects ofasecondary-treatedBKME in two different species of fish:Carassius auratus and Dicentrarchus labrax. Both species were exposed to different concentrations of secondary-treated effluent (1%, 10%, 25%, 50%, 100%) in semi-static tests under controlled laboratory conditions. At the end of the experimental period (21 days), samples of livers were collected for CYP1A determination and histopathological evaluation. The results show significant changes (p<0.05) of CYP1A induction in carp exposed to 50% and in sea bass exposed to 25% of the effluent. Histopathological alterations were also observed according to the different concentrations of the tested effluent suggesting that tested BKME cause damage to exposed organisms.